If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 3) = 4(1 + x) Reorder the terms: 3(3 + x) = 4(1 + x) (3 * 3 + x * 3) = 4(1 + x) (9 + 3x) = 4(1 + x) 9 + 3x = (1 * 4 + x * 4) 9 + 3x = (4 + 4x) Solving 9 + 3x = 4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 9 + 3x + -4x = 4 + 4x + -4x Combine like terms: 3x + -4x = -1x 9 + -1x = 4 + 4x + -4x Combine like terms: 4x + -4x = 0 9 + -1x = 4 + 0 9 + -1x = 4 Add '-9' to each side of the equation. 9 + -9 + -1x = 4 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = 4 + -9 -1x = 4 + -9 Combine like terms: 4 + -9 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5
| 2(x+3)=3x-1 | | -1-6m= | | 15m=50m+40000 | | 2a-5=13 | | 4-(3-x)=2 | | 6=-1(7-c) | | k/21=15 | | 7y+2(y-3)=6(y+1)-4 | | 3.8-4.9x+0.1x=2.4y+0.2 | | -17+x=-9 | | 11a^2-9ab+4a= | | 6u-2u+12u=-16 | | 8+2x=20-4x | | -2(-7x+1)=5x+34 | | 7+3g-4h+3h-10= | | -9=17x | | 16=2(d-5) | | 3+6x=4x-7 | | 4x-4b=1x | | -4q-2=-18 | | -17*x=-9 | | 1.25p-0.2p+12=6 | | 5-4x=5-5x | | -7(-v-11)-v=-11(9v-7) | | (X^2)-6x-23=0 | | 6d-6d+5d+1=16 | | 45=12+3(t-8)-6 | | -2x=8.8 | | 4(-9)-70=12(-9)+2 | | 3(65)=(65)+10 | | 2(x-5)-12=10(4x+8) | | 20=7-c |